2006
DOI: 10.1634/theoncologist.11-3-263
|View full text |Cite
|
Sign up to set email alerts
|

Large Granular Lymphocyte Leukemia

Abstract: Learning ObjectivesAfter completing this course, the reader will be able to:1. Discuss the basic principles of molecular and cellular biology of LGL leukemia. Describe distinct clinical entities among disorders ofLGLs.3. Discuss the diagnostic criteria for T-cell LGL leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
207
2
19

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(228 citation statements)
references
References 75 publications
0
207
2
19
Order By: Relevance
“…Such an association has been frequently reported with rheumatoid arthritis or with less specific autoimmune features such as positivity to autoantibodies (e.g. antinuclear antibodies, antineutrophils) in the absence of a clear autoimmune disease [2]. Here, we report a case of T cell LGL leukemia in which a concurrent diagnosis of Sjögren’s syndrome was made.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Such an association has been frequently reported with rheumatoid arthritis or with less specific autoimmune features such as positivity to autoantibodies (e.g. antinuclear antibodies, antineutrophils) in the absence of a clear autoimmune disease [2]. Here, we report a case of T cell LGL leukemia in which a concurrent diagnosis of Sjögren’s syndrome was made.…”
Section: Introductionmentioning
confidence: 56%
“…The most common autoimmune disorder associated with T cell LGL leukemia is rheumatoid arthritis, but other autoimmune disorders have been described in the literature [2]. These include cases of thrombotic thrombocytopenic purpura, pure red cell aplasia, Behcet’s syndrome and Sjögren’s syndrome [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that T-LGL leukemia is an indolent disease that requires no treatment at the time of presentation in the majority of patients, 70% will ultimately require therapy at a later date. The most common indications for therapy include life-threatening infections, severe neutropenia, symptomatic anemia or thrombocytopenia, and severe B symptoms [2,9]. Because of the rarity of T-LGL leukemia, very few prospective clinical trials have been reported, and current treatment strategies are based on anecdotal case reports and small retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the rarity of T-LGL leukemia, very few prospective clinical trials have been reported, and current treatment strategies are based on anecdotal case reports and small retrospective studies. In previous reports, treatment with immunomodulation, corticosteroids, low-dose methotrexate, cyclophosphamide, and cyclosporine A with or without purine analogues are all described [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation